Simultaneous high-precision, high-frequency measurements of methane and nitrous oxide in surface seawater by cavity ring-down spectroscopy - Brown, Ian J.; Kitidis, Vassilis; Rees, Andrew P. (Frontiers in Marine Science, 2023)
An automated system was developed using commercially available Cavity Ring-Down Spectroscopy (CRDS) technology (Picarro LTD., G2508) which was interfaced to a custom-made system which automated the equilibration and analysis of seawater dissolved nitrous oxide (N2O) and methane (CH4). The combined system was deployed during two research cruises in the Atlantic Ocean, which combined covered 16,500 kms, one on a west to east transect between the United States and Europe at approximately 24°N, the second was a north to south transect which covered approximately 70° of latitude between the Tropic of Cancer and the Southern Ocean. Semi-continuous measurements using the CRDS (Approx. 73,000) were compared to discretely collected samples (n=156) which were analysed using gas chromatography (GC) with flame ionisation detection for CH4 and electron capture detection for N2O. Excellent agreement between the two approaches, though with an increase in analytical precision offered by CRDS compared to GC gives great confidence in the applicability of the CRDS system, whilst the significant (2 to 3 orders of magnitude) increase in measurement frequency offer an opportunity to greatly increase the number of dissolved N2O and CH4 data that are currently available. Whilst identifying a number of small-scale features, deployment during this study showed that whilst the surface of large areas of the Atlantic Ocean were in-balance with the overlying atmosphere with respect to N2O, the most of this region was offering a source of atmospheric CH4.